Accuracy of leg length and femoral offset restoration after total hip arthroplasty with the utilisation of an intraoperative calibration gauge. Issue 3 (May 2020) - Enke, Oliver; Levy, Yadin D; Bruce, Warwick JM
Background: Offset and leg length (LL) restoration are critical for the achievement of a stable, well-functioning hip following total hip arthroplasty (THA). Several techniques are described in the literature, including a hip calibration gauge. We question whether meticulous preoperative planning of a specific surgical technique in combination with the utilisation of a calibration gauge can provide an accurate offset and LL restoration. Methods: Retrospective review of 101 unilateral THAs via a posterior approach by a single surgeon. Preoperative radiographic LL and offset were radiographically calculated. Intraoperatively prior to hip dislocation a calibration gauge was used to measure LL and offset with a pin inserted into the iliac crest acting as a static referencing point. All had pelvis x-ray performed 6 weeks postoperatively. A literature review was conducted to establish average postoperative LL/offset values for statistical comparison. Results: The average absolute postoperative leg-length discrepancy (LLD) was 2.51 mm compared to preoperatively 3.54 mm ( p = 0.018). A total of 93.1% and 100% had LLD of ⩽5 mm and ⩽10 mm, respectively. The mean postoperative offset difference was 2.39 mm. The investigated LLD and offset results were comparable with literature data of studies utilising an intraoperative measuring device. LLD was significantly decreased when compared to a free-hand technique (LLD 4.42 mm, p < 0.001). Conclusion: The technique utilising preoperative templating, intraoperative offset verification together with the use of hip calibration gauge yielded accurate LLD and offset restoration as in the literature. Precise offset restoration, which often is a neglected issue, can lead to better abductor vector restoration, hip function and less pain.